Menelusuri Sejarah Kuliner Jambi sebagai Inventarisasi Aset dan Promosi Wisata Kuliner di Provinsi Jambi - Nirwan Il Yasin; Nelly Indrayani; Fatonah Nurdin (Ideas Publishing, 2022)
Tracing the history of Jambi culinary as an inventory of assets and promotion of culinary tourism in Jambi Province is very important, lifting the identity of the Jambi region. This research aims to find out the development of Jambi culinary. In addition, taking steps, making a legal umbrella so that Jambi culinary is not lost from the next generation. The method used in this research is qualitative method and field interview with descriptive form. The results of this study indicate that the potential in developing culinary tourism in the Jambi region such as the Jambi Muaro Temple festival, Kerinci Lake festival, Lake Sipin festival. Promotional activities by forming a calendar of scheduled tourism activities, thus attracting tourism interest from inside and outside who want to know about Jambi culinary.